Intellectual property rights for publishing materials intended for e-learning * Limitation of liability between the publisher and author * (Journal of Human Sciences, 2021)
Moral trade has come to occupy a significant place in the field of international relations, especially after the recognition of copyright by its universal nature, which makes it exist and be decided everywhere, therefore if the publication contract has the international characteristic as previously mentioned it was necessary to define the law that will govern it, as The publishing contract does not have a national dimension, but rather it has an international dimension, and this is because of the very important importance of ideas and information, especially in today's world, which has become based on e-learning and which is required by distance education, and since the basis of the relationship is the will of its parties according to the principle of the authority of the will, In this sense, Both jurisprudence and jurisprudence stipulate that the international contract is subject to the law chosen by the contracting parties, but it may happen that the parties remain silent in defining this law, so what is the solution or alternative to the law of will in this case ?, Also, the liberalization of international trade created a kind of rule The transboundary movement affected the international contract, so how does it resonate with the international contract, the subject of which is the exploitation of copyright.  If the text of Article 84 of Ordinance 03-05 relating to Algerian copyright and related rights is defined, the publishing contract is defined as: “The publishing contract is the contract whereby the author assigns the publisher the right to reproduce many copies of the work according to agreed terms and in return for a reward for publishing it and distributing it to Audience for publisher account. " For this we raise the following problem in what is the responsibility and obligations that fall on the publisher in the scientific secretariat of the literature approved as references in e-learning?